MiR‐377 Regulates Inflammation and Angiogenesis in Rats After Cerebral Ischemic Injury. Issue 1 (22nd September 2017) - Fan, Yiling; Ding, Shenghao; Sun, Yameng; Zhao, Bing; Pan, Yaohua; Wan, Jieqing
ABSTRACT: Ischemic stroke is the leading cause of disabilities worldwide. MicroRNA‐377 (miR‐377) plays important roles in ischemic injury. The present study focused on the mechanisms of miR‐377 in protecting ischemic brain injury in rats. Cerebral ischemia was induced by middle cerebral artery occlusion (MCAO) in rats. Primary rat microglial cells and brain microvascular endothelial cells (BMECs) were exposed to oxygen‐glucose deprivation (OGD). The concentrations of cytokines (TNF‐α, IL‐1β, IL‐6, IFN‐γ, TGF‐β, MMP2, COX2, and iNOS) in the culture medium were measured by specific ELISA. Tube formation assay was for the in vitro study of angiogenesis. Luciferase reporter assay was performed to confirm whether VEGF and EGR2 were direct targets of miR‐377. The MCAO rats were intracerebroventricular (ICV) injection of miR‐377 inhibitor to assess its protective effects in vivo. MiR‐377 levels were decreased in the rat brain tissues at 1, 3, and 7 d after MCAO. Both microglia cells and BMECs under OGD showed markedly lower expression levels of miR‐377 while higher expression levels of EGR2 and VEGF compared to those under normoxia conditions. Knockdown of miR‐377 inhibited microglial activation and the release of pro‐inflammatory cytokines after OGD. Suppression of miR‐377 promoted the capillary‐like tube formation and cell proliferation and migration of BMECs. The anti‐inflammation effect of EGR2 and the angiogenesis effect of VEGF were regulated by miR‐377 after OGD. Inhibition of miR‐377 decreased cerebral infarct volume and suppressed cerebral inflammation but promoted angiogenesis in MCAO rats. Knockdown of miR‐377 lessened the ischemic brain injury through promoting angiogenesis and suppressing cerebral inflammation. J. Cell. Biochem. 119: 327–337, 2018. © 2017 Wiley Periodicals, Inc. Abstract : Our study demonstrates that knockdown of miR‐377 prevents ischemic brain injury through suppressing cerebral inflammation but promoting angiogenesis, suggesting an interesting prospect for using miR‐377 as a method for stroke therapy.